Arctic-like Rabies Virus, Bangladesh ... : فيروس داء الكلب الشبيه بالقطب الشمالي، بنغلاديش ... - Khondoker Mahbuba Jamil; Kawsar Ahmed; Md. Bellal Hossain; Takashi Matsumoto; Mohammad Azmat Ali; Sohrab Hossain; Shakhawat Hossain; Aminul Islam; Mohammad Nasiruddin; Akira Nishizono (OpenAlex, 2012)
Arctic/Arctic-like rabies virus group 2 spread into Bangladesh ≈32 years ago. Because rabies is endemic to and a major public health problem in this country, we characterized this virus group. Its glycoprotein has 3 potential N-glycosylation sites that affect viral pathogenesis. Diversity of rabies virus might have public health implications in Bangladesh. ... : انتشرت مجموعة فيروسات داء الكلب 2 الشبيهة بالقطب الشمالي/القطب الشمالي إلى بنغلاديش منذ 32 عامًا تقريبًا. نظرًا لأن داء الكلب متوطن ومشكلة صحية عامة رئيسية في هذا البلد، فقد ميزنا مجموعة الفيروسات هذه. يحتوي البروتين السكري على 3 مواقع محتملة لربط N - glycosylation التي تؤثر على التسبب في الأمراض الفيروسية. قد يكون لتنوع فيروس داء الكلب آثار على الصحة العامة في بنغلاديش. ...